Investment as a transmission mechanism from weak demand to weak supply and the post-crisis productivity slowdown - Ollivaud, Patrice; Guillemette, Yvan; Turner, David (Paris, 2018)
"Current weak labour productivity growth in many OECD countries reflects historically weak contributions from both total factor productivity (TFP) growth and capital deepening. The slowdown in trend productivity growth in the pre-crisis period is mostly explained by a long-established slowdown in TFP growth, but since the crisis the further deceleration is mainly due to weak capital deepening, a development apparent in practically every OECD country. Much of the weakness in the growth of the capital stock since the financial crisis can be explained by an accelerator response of investment to continued demand weakness, leading in turn to a deterioration of potential output via a hysteresis-like effect. For the most severely affected economies, the financial crisis is estimated to have reduced potential output by more than 2% via this transmission mechanism. In many OECD countries, declining government investment as a share of GDP has further exacerbated post-crisis weakness in capital stock growth, both directly and probably indirectly via adverse spillover effects on business investment. Finally, over a period when the use of conventional macro policy instruments was constrained, the slower pace of structural reform represents a missed opportunity, not least because more competition-friendly product market regulation could have boosted both investment and potential growth."